Investigation of students’ self-regulation skills, motivation and disorientation in smart mooc - Yılmaz, Ramazan; Karaoğlan Yılmaz, Fatma Gizem; Yılmaz, Ramazan; Karaoğlan Yılmaz, Fatma Gizem (International Azerbaijan Congress on Life, Social, Health, and Art Sciences, 2022)
Students who have not developed self-directed skills in online learning environments may face problems such as not knowing what to do. Students in this situation need the advice and guidance of external support, such as the teacher. In MOOC environments, students are expected to make their own decisions, orient themselves, develop their own study strategy and make their own self-assessments. For this reason, students with low motivation who have not developed self-directed skills may fail to take courses at MOOCs. From this point of view, it is understood that there is a need for smart MOOC environments that determine the current situation and needs of the student with learning analytics, advise and guide the student through the recommendation system in line with these needs. According to this, students’ self-regulation skills, motivations and disorientation in hypermedia were examined within the scope of the research. The research was conducted on 116 university students who took the statistical methods in education course in the smart MOOC environment. Research data were obtained through the Online Self-Regulation Questionnaire, MSLQ and Disorientation Scale. Research findings revealed that students using the smart MOOC environment had high self-regulation skills, MSLQ scores were moderate, and they were less likely to disorientation in hypermedia environments. When the relations between the scales are examined, it is revealed that there is a small negative correlation between disorientation scale – online self-regulation questionnaire, a moderate negative correlation between disorientation scale – MSLQ, and a strong positive correlation between online self-regulation questionnaire- MSLQ. Various suggestions were made in line with the research findings.
Keywords: Smart MOOCs; learning dashboard; learning analytics; recommendation system; lf- regulation skills; disorientation in hypermedia; motivation; Öğrenme panosu; Öğrenme analitiği; Hiper ortamda oryantasyon bozukluğu; Motivasyon